The water quality analysis in tap water between University Malaysia Kelantan campus Jeli and campus Pengkalan Chepa - M M Kamal Yassin Abdul Rashid (2014)
Metal contamination in water is a major problem in the determination of water quality. Apparently, tap water qualities in many countries are affected by industrialization. The objective of this study was to detect metal concentration in tap water in the University Malaysia Kelanta Campus Jeli and Campus Pengkalan Chepa . This study has been done in order to determine the concentration of Copper, Zinc and Manganese in Univesity Malaysia Kelantan Campus,specificly Campus Jeli and Campus Pengkalan Chepa. The study was carried out by collecting 18 samples of water samples from the study area ,2 area and 3 point each for water analysis.Tap water samples were collected from three different locations at each location. The six sampling locations were Pengkalan Chepa campus, block A, block B, Block C, and Campus Jeli Block A,block B and block G. Samples were analysed using atomic absorption spectrometry to determine the concentration of dissolved metal. The metal analysis was done to detect zinc, manganese and copper. The results obtained were compared with guidelines for drinking water quality such as the Environmental Protection Agency (EPA) and World Health Organization (WHO) guidelines. The study showed that the piping system and water source in Pengkalan Chepa and Jeli affected levels of Zinc and copper in the water, but not manganese.